The impact of cycleanine in cancer research: a computational study - Nwaefulu, Ogochukwu Ngozi; Al-Shar'i, Nizar A; Owolabi, Josephine Omonkhelin; Sagineedu, Sreenivasa Rao; Lim, Chee Woei; Lam, Kok Wai; Islam, Mohammad Kaisarul; Jayanthi, Sivaraman; Stanslas, Johnson (Springer, 2022)
Cancer is imposing a global health burden because of the steady increase in new cases. Moreover, current anticancer therapeutics are associated with many drawbacks, mainly the emergence of resistance and the severe adverse effects. Therefore, there is a continuous need for developing new anticancer agents with novel mechanisms of action and lower side effects. Natural products have been a rich source of anticancer medication. Cycleanine, a natural product, was reported to exert an antiproliferative effect on ovarian cancer cells by causing apoptosis through activation of caspases 3/7 and cleavage of poly (ADP-ribose) polymerase to form poly (ADP-ribose) polymerase-1 (PARP1). It is well-established that PARP1 is associated with carcinogenesis, and different PARP1 inhibitors are approved as anticancer drugs. In this study, the cytotoxic activity of cycleanine was computationally investigated to determine whether it is a PARP1 inhibitor or a caspase activator. Molecular docking and molecular dynamics (MD) simulations were utilized for this purpose. The results showed that cycleanine has a good binding affinity to PARP1; moreover, MD simulation showed that it forms a stable complex with the enzyme. Consequently, the results showed that cycleanine is a potential inhibitor of the PARP1 enzyme.